Pengembangan Lembar Kerja Peserta Didik Bernuansa Kearifan Lokal pada Pembelajaran Matematika - Annajmi; Arcat; Lusi Eka Afri; Nurrahmawati (LPPM Universitas Advent Indonesia, 2024)
Limited mathematics learning resources in schools mean that teachers only use textbooks and worksheets provided by the school. This is also a lack of teacher knowledge and skills in utilizing a variety of learning resources in mathematics learning. This research aims to produce LKPD with nuances of local Malay wisdom in Rokan Hulu, Riau. This type of research is research and development (R&D). The development of this LKPD follows the ADDIE development model. The LKPD developed met the validation criteria, namely an average of 4.41 was obtained in the valid category. This shows that this LKPD is suitable for use in mathematics learning. Implementation of the use of LKPD in mathematics learning through the classroom action research stage, which was carried out by the mathematics subject teacher at SMPN 1 Rambah, which was carried out in 2 cycles. The test results in cycle I were 24 students or 75% complete and 8 students or 25% incomplete. The test results in cycle II showed that all students completed, namely 32 students or 100% completion. This shows that this LKPD is effective and practical for use in mathematics learning. Thus, this LKPD meets the criteria, is valid, practical and effective for use in mathematics learning.